2018
DOI: 10.1371/journal.pone.0205508
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of cyclooxygenase-2 in patients suffering from esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the aggressive malignancies and mechanisms underlying its pathogenesis remain unclear. Cyclooxygenase-2 (COX-2) enzyme system plays a crucial role in many gastrointestinal malignancies and is an important regulator of cell growth, proliferation, apoptosis, differentiation and transformation. More precise outcome of COX-2 in ESCC is less investigated. In this study we investigated the risk factors of ESCC and expression of COX-2 in Carcinoma in situ (CIS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that PGE2 promotes TAMs formation in glioblastoma ( 33 ), colorectal cancer ( 35 ), ovarian cancer ( 37 ), neuroblastoma ( 38 ) and prostate cancer ( 39 ). Based on the accumulation of macrophages ( 40 ) and differential expression of COX-2 in ESCC ( 41 ), it could be inferred that above correlation may also exist in the TME of ESCC. Our data supported this opinion and also suggested that besides tumor cell-derived PGE2, macrophage-derived PGE2 may also make contribution to M2-TAMs polarization through PPARγ-OXPHOS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that PGE2 promotes TAMs formation in glioblastoma ( 33 ), colorectal cancer ( 35 ), ovarian cancer ( 37 ), neuroblastoma ( 38 ) and prostate cancer ( 39 ). Based on the accumulation of macrophages ( 40 ) and differential expression of COX-2 in ESCC ( 41 ), it could be inferred that above correlation may also exist in the TME of ESCC. Our data supported this opinion and also suggested that besides tumor cell-derived PGE2, macrophage-derived PGE2 may also make contribution to M2-TAMs polarization through PPARγ-OXPHOS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan has poor socioeconomic status, use of naswar specially in Pukhtoons of Baluchistan that has attributed towards high rates of squamous cell oesophageal carcinoma in this population setting. 2,7,11,12 In Pakistan OC is very common in some areas and experience regional variability. It is more common in Northwest frontier province (NWFP).…”
Section: Introductionmentioning
confidence: 99%